Effect of the double school day on the academic performance of Colombian students: An empirical analysis to inform the full day policy - Claudia Patricia Ovalle-Ramirez (Arizona State University, 2018)
To establish the effect of the school shift on students' performance in Quantitative Reasoning, Science and Reading (measured with standardized test SABER11) a quasi-experimental research design was implemented. In order to obtain matched samples Propensity Score Matching was used. Data comes from both single shift schools (including either Full time shift, Morning shift or Afternoon shift) used as control groups (or counterfactuals) and Double shift schools (including both Morning and Afternoon shifts, but serving different students) as experimental group. National Databases such as National Educational Survey C-600, National Ministry of Education SIMAT, and National Standardized Tests (SABER11) were used. The results indicate that the double shift schools increase between 2% and 6% of a standard deviation of the Quantitative Reasoning results, between 1% and 5% in Science and between 1% and 6% in Critical Reading. Institutions that have a single day, whether full shift, morning shift or afternoon shift, showed a decrease in test results. These results can inform those who make educational policies and the countries where they plan to implement the extension of the school day as a strategy of educational quality and equity.